Vll Edition of Quincke´s Scholarship: Lecture Highlights - Padrón-González, Alexander Ariel; Lumpuy-Castillo, Jairo; Rodríguez-Pérez, José Alejandro; Pérez-Vallín, Vanesa; Mirabal-Viel, Alejandro; González-Losada, Cristóbal; Castillo-González, William; Dorta-Contreras, Alberto Juan (Revista Cubana de Investigaciones Biomédicas, 2020)
Introduction: Quincke´s Scholarship deals with themes related to neuroimmunology and the complement system. Objective: Describe the most recent advances of the Vll Edition of Quincke´s Scholarship. Matherial and Methods: Publications pertaining to Quincke´s Scholarship were selected and reviewed from the work group of the Central Lab of Cerebrospinal Liquid (LABCEL). Results: The principal topic was the C1q protein; initiator of the classic complement pathway. The analysis of the molecular concentration of this protein, its transference from blood to cerebrospinal fluid (LCR) and the correlations between the concentration of C1q protein in LCR and the quotient of albumin (QAlb) between LCR and plasma made possible the hypothesis that an intrathecal synthesis of the C1q could be possible in patients. The reibergram is useful to evaluate the immune response in patients with neurological manifestations caused by the dengue virus, and patients with multiple sclerosis among other ones. Conclusions: The Vll Edition of Quincke´s Scholarship demonstrated some news findings in C1q with the employment of the reibergram.